The Danish subsidy scheme for non-commercial local stations - Jauert, Per (Javnost (Ljubljana), 2003)
In 1998 the modality of the subsidy scheme for non-commercial local radio and television stations in Denmark was changed in favour of funding specific programs rather than distributing the biggest part of the funding based on programming hours, as was previously done. In relation to these changes, the authors of this article were commissioned by the Ministry of Culture to monitor and evaluate the development from 1999 to 2000, with special attentionto the question of enhanced program quality as an outcome of the changes. According to the agreement with the ministry, the project consisted basically of four elements: the administrative level; a profile of selected stations; qualitative analyses of selected programs from the stations included; and finally the audience. The evaluation project was completed in spring 2002, and in this article some of the findings and methodological approaches are presented. In the first part, the predominantly quantitative findings regarding the economic ramifications of the change in the subsidy system are summarised together with the most important administrative questions. In the second part a case study of a television station is selectedout of nine in-depth studies for presentation. The general aims of thearticle are to illustrate the methodology conducted (combing quantitative investigations, content analyses and audience research in the form of focus group interviews) and to present an overall summary of findings from the project.
Keywords: Danska; Denmark; radio; lokalne skupnosti; mass media; množični mediji; television; televizija; financiranje; subvencioniranje; subvencije